Chronic prostatic inflammation as a prognostic marker for post-operative improvement in clinical parameters after transurethral resection of prostate - Venkatesh Velivela; Ifrah Ahmad Qazi; Tappa Mahammad Mustaqrasool; Vedamurthy Reddy Pogula; Reddy, Sandeep Kumar (Asian Journal of Medical Sciences, 2022)
Background: Medical therapy of prostatic symptoms and reduce study on benign prostatic hyperplasia (BPH) recently demonstrated a link between histological prostatic inflammation and prostate enlargement or symptoms scores. Aims and Objectives: Prognostication of symptoms of lower urinary tract based on pathological diagnosis following transurethral resection of prostate (TURP). Materials and Methods: This was a prospective observational study. A total of 60 BPH patients who underwent TURP were studied; 30 patients in each group, BPH without inflammation (Group I), and BPH with inflammation (Group II). Pre-operative and post-operative international prostate symptom score (IPSS), overactive bladder symptom score (OABSS), and uroflowmetry were compared in both groups. Chronic prostatic inflammation was assessed by the grade (lymphocyte density), extent (lymphocyte distribution), and location of inflammation. Results: The prostate volume was significantly higher in Group II as compared to Group I (53.2±1.29 vs. 50.87±1.48). The improvement in IPSS and OABSS in each group, before and after surgery, was significant but the between-group difference was not significant. The post-operative voided volume (in ml) in Group I was 273.27±52.34 and in Group II, it was 289.47±34.25 (P=0.03). The post-operative post-void residual volume (in ml) was 21.97±2.55 in Group I and 13.28±2.11 in Group II (P=0.017). The post-operative Qmax (ml/s) in Group I was 15.41±2.1 and in Group II it was 19.28±2.11. (P=0.041). Conclusion: Surgical resection of the prostate helps in a higher degree of improvement in post-operative clinical parameters in BPH patients with inflammation.